Antagonism of Trichoderma Species to Polyporus sanguineus - an Incitant of Bamboo Decay - Kundu, Aruna; Chatterjee, N. C. (Indian Forester, 2003)
Three biocontrol agents: Trichoderma viride , Trichoderma lignorum , Trichoderma harzianum were evaluated in-vitro to assess their mode of antagonism against a wood rot fungus Polyporus sanguineus. T. harzianum was the most effective in causing significant suppression of growth of P. sanguine us through competition and through the production of volatile antibiotics followed by T. lignorum and T. viride. Their non-volatile antibiotics suppressed 100% growth of the test fungus. The antagonists were also mycoparasitic on P. sanguineus. Maximum growth inhibition of the test fungus occurred after 7 days of incubation. The biocontrol agents appeared to have potential for application in practical and economic control of bamboo rot by Polyporus sanguine us.